THE ESSENTIAL NERUDA. Edited by Mark Eisner. Pp. 199. San Francisco: City Lights 2004. Pb. 16.95. - Johnson, Penny (POLISSEMA – Revista de Letras do ISCAP, 2019)
In April 2004 an independent American publisher, City Lights, based in San Francisco, published a compilation of translations of fifty poems by the Chilean poet laureate, Pablo Neruda. This publication, which was part of a project to celebrate the one hundred years since the poet’s birth, coincided with the National Poetry of the Month celebrations in the US. As the editor of the collection, Mark Einser, said the book is a complement to a more comprehensive 1000-page volume of Neruda’s poetry in English translation titled The Poetry of Pablo Neruda, published in New York in 2003 by Farrar, Straus and Giroux.